A heuristic approach for near optimal truncated sequential test of exponential distribution. Issue 4 (2nd October 2018) - Hu, Sigui; Wang, Honglei
Abstract: Optimal truncated sequential test of the exponential distribution is studied in this paper. Definitions and relative concepts of optimal truncated sequential test are discussed. A heuristic approach, sample space sorting method (SSSM) and the procedures are established to solve a near optimal truncated sequential test. Comparing with the test plans provided by international standard IEC 61124 (2012 ) and Russian national standard GOST R 27.402 (1995 ), the results show that the near optimal tests proposed in this paper can keep the error probabilities almost equivalence to the nominal error levels and save more synthetical expected test times and maximum expected test times simultaneously.